EVALUATION PROGRAM APPROACH IN EDUCATION - Ira Rahmayuni Jusar; Ambiyar Ambiyar; Ishak Aziz (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This paper describes the evaluation program approach in education. This approach is carried out to evaluate the student’s achievement level in learning. This activity needs to be conducted to help teachers thoroughly so that inputs and processes in learning can be contained in the learning process. The use of method is applied based on a literature review through meta-analysis derived from the results of reviewing journals regarding the implementation of the evaluation program approach in learning that has the same topic in this paper, analyzed, and compared to the review results, which are described in good language. The research result indicates eight approach models in the evaluation of educational programs, which are the CIPP model, Provus model, Stake model, Kirkpatrick model, Brinkerhoff model, Congruence model, Illuminative model, and Logical model. The CIPP model is an approach that teachers often use because it includes context, input, process, and outcome evaluation. The results of applying this approach model can be carried out thoroughly so that it can be applied to every learning subject.